The Source of Salt in Rajasthan - an Investigation of the Salt Lake of Didwana - Paliwal, B S (Annals of Arid Zone, 2016)
The origin of salt in different salt lakes of Rajasthan had been a long controversial problem, which remained unsolved inspite of numerous efforts made by a number of workers. The recent investigation carried out in the salt lake of Didwana as well as the occurrence of halite in it and the Bikaner area, gave a new turn to the problem. The investigation revealed that the source salt in all the salt lakes of Rajasthan appears to be associated with the Aravalli rocks, probably in the form of salt domes and intrusives, situated below recent deposits at a good depth. This salt appears to be Precambrian evaporitic in origin which must have been pushed out at a number of places, during different phases of tectonic deformation of the Aravalli rocks in western Rajasthan.